Accounting : building business skills - Kimmel, Paul D. (Milton, Qld. : John Wiley & Sons Australia, 2005)
Maintains the balance between a user and preparer perspective effectively integrating real financial data and business decisions throughout the material and presenting a macro view of accounting information through the use of real company information and financial statements.
Previous ed.: Financial accounting: tools for business decision making, 2003.
Includes index.
Keywords: Accounting -- Problems, exercises, etc